Career Decision Making in College Students - Abdullah, Sri Muliati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2018)
This study aims to assess the problem of the student's career decision making. The assessment focused on student decisions that are taken on issues that netted a career in the study of student career readiness and maturity. Retrieving data using the theme documentation studies 642 career counseling college graduate job seekers (Fresh graduate) and of note other researchers who have an interest in the study of career. From the results of scrutiny of the results of the study, researchers chose to study the career decision making as the most critical issue that needs to be studied. Students need to understand the problem of why they need education and work after graduation, find and use information, look for an alternative, choose a destination and make a plan.